Recovery of nickel, phosphorus and nitrogen from electroless nickel-plating wastewater using bipolar membrane electrodialysis. (1st January 2023) - Liu, Yaoxing; Wu, Xiaoyu; Wu, Xiaoyun; Dai, Liping; Ding, Jianguo; Ye, Xin; Chen, Riyao; Ding, Rui; Liu, Jianxi; Jin, Yanchao; Van der Bruggen, Bart
Abstract: Electroless nickel-plating (ENP) wastewater is challenging to treat because of its complex composition. This study used bipolar membrane electrodialysis (BMED) to remove and recover Ni 2+, NH4 +, total phosphorus (TP) and NO3 − from ENP wastewater. The results show that current density significantly affects ion removal and recovery, current efficiency, specific energy consumption and ion migration velocity. When the current density was 20 mA/cm 2, the removal ratios of Ni 2+, NH4 +, TP and NO3 − were 100%, 98.6%, 99.3% and 100% after 14 h, respectively, and their recovery ratios were 92.6%, 75.5%, 94.5% and 90.6%, respectively. The removal kinetics analysis showed that the removal of Ni 2+, NH4 +, TP and NO3 − was consistent with the zero-order kinetics process. The current efficiency variated from 42.5% to 39.0% and 37.7%, and the specific energy consumption decreased from 1.67 to 1.38 and 1.32 kW h/mol with the equipped wastewater compartments increased from one to two and three in a BMED system. Post treatment, Ni 2+ was recovered as Ni(OH)2, with a purity of 82.6% (commercial Ni(OH)2 purity = 90%). TP was recovered as struvite with a purity of 95.3%, and the physicochemical properties of the obtained struvite were similar to commercial struvite. NH4 + was recovered as (NH4 )2 SO4 and NH3 H2 O. Therefore, BMED is an effective method to recover Ni 2+, TP and NH4 + from ENP wastewater. Graphical abstract: Image 1 Highlights: Electroless nickel-plating wastewater was treated using a BMED system. Ni 2+ was recovered in the form of Ni(OH)2 with a purity of 82.6%. Total phosphorus was recovered in the form of struvite with a purity of 95.3%. NH4 + was recovered in the form of (NH4 )2 SO4 and NH3 .H2 O.